The Effect of Workload and Teamwork on Organizational Productivity - Wahyu Abadi; Setyo Riyanto (Jurnal Economic Resource, 2021)
Learning the science of human resource management is very important, where we can find out how to treat humans well so that they can become valuable assets in the future. This article discusses how workload and teamwork affect organizational productivity. Comparing several existing literature and theories proves that the two have a significant relationship. Where both affect employee performance, good teamwork will result in a small workload to create good organizational productivity and vice versa. This study aims to determine and analysed the effect of workload and teamwork on organizational productivity simultaneously or partially. The population in this study is company XYZ, one of the private companies in Jakarta which is engaged in Chemical Raw Materials. The sample in this study was selected using a random sampling method with 38 respondents from one division in the company. The data analysis method used is multiple linear regression analysis. The research results obtained are simultaneously Workload and Teamwork affect the productivity of the Organization. Meanwhile, partially Teamwork affects organizational productivity. However, Workload has no effect on the Productivity of the organization.